Telecommunications for the needy: how needed are they? - Cardoso, G.; Puga, P.; Espanha, R.; Mendonça, S. (Informatica Economica Journal, 2009)
Telecommunications, mobile and non-mobile, play a major role in our society, but their role as tools for escaping poverty remains a policy agenda still with room for progress both in Europe and around the World. Some groups in society, like the needy, have difficulties in accessing and using such technologies in ways that mirror the debates of the late 90s over the "digital divide". For some groups, like the needy, it would be more exact to address the concept of digital poverty rather than digital divide, because without access to telecommunications one might not have the same degree of opportunities to leave poverty or not to fall into poverty [34] [3] [4]. The goal of this paper is to scope the problem by departing from the Portuguese case study. Our research is empirical and highlights the telecommunication ownership and expenditures of the Portuguese population, and specially the most fragile segments within it. Such an effort is undertaken while not ignoring major issues of political economy of the contemporary globalizing networked society. Our main argument in this paper is that, if telecommunications are a needed tool for the lower income segments of the population, that is the needy, a debate around digital poverty associated to mobile telecommunications is needed in Europe too and to address such issues we need public policy commitments.